Pengaruh Waktu Ekstraksi pada Pektin Ampas dan Kulit Buah Melon (Cucumis Melo L. var. Sky Rocket) - Parasu, Risang; Aisyah, Ersa Amalia; Nurhadianty, Vivi; Dewi, Luthfi Kurnia (Fakultas Teknik, Universitas Brawijaya, 2021)
The purpose of this study was to determine the effect of extraction time on yield, methoxyl content and degree of esterification. In this study, the raw materials used are melon pulp and peel. The process of obtaining pectin from raw materials is reflux extraction with the extraction time of 60, 90, and 120 minutes using citric acid pH 2.5 as a solvent. The result shows pectin yield for each extraction time of 60, 90, and 120 minutes to be 4.16%, 11.91%, and 5.49% for melon pulp and 2.29%, 6.86%, and 3.57% for melon peel, respectively. Methoxyl content of pectin increases with increasing extraction time to be 2.05%, 3.41%, and 3.78% for melon pulp and 2.17%, 2.73%, and 3.72% for melon peel, respectively. Pectin esterification degree decreases with increasing extraction time to be 48.53%, 44%, and 33.52% for melon pulp and 46.67%, 39.29%, and 30.93% for melon peel, respectively. Methoxyl content value of <7% and esterification degree of <50% shows pectin obtained from this study is the low-methoxyl pectin.